(3GdJfXje GdbGfhfj dYbO GdJQNjU HGSJZdGd HQGAI GdGNJQGY aj eLGd fbd GdJcfhdhLjG (B: s (3OQGSI aj VhA GdbGfhf GdchjJj hGJaGbjI GdJQHS (B/ s - (3LQGM Ydj YHOGddg GdeWjQjs; (3Ndjd ajcJhQ JGOQS s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3jYJHQ fehPL JQNjU HQGAGJ GdCNJQGY ef CaVd GdWQb GdfGbdI ddJcfhdhLjG ShGA Hjf GdOhd GdeJbOeI HYVgG GdHYV Ch Hjf GdOhd GdeJbOeI h GdOhd GdfGejI GdJj JaJbQ GdbOQI GdUfGYjI hGdNHQI GdJbfjI , hdcf jTJQW dcj jchf YbO GdJQNjU fGLkMG aj GdMGdg GdCNjQI Cf jHMK GdeSJhQO Yf GdJcfhdhLjG GdJi JdGFe WHjYI HdOg ShGA ef GdfGMjI GdCbJUGOjI Ch GdSjGSjI Ch GdLZQGajI(B: (3hCf jJVef GdYbO HYV GdTQhW GdJj Jcad GdGfJbGd GdGeKd ddJcfhdhLjG GdeQNUg hefgG Ydi SHjd GdeKGd TQW GdeSGYOI GdafjI(B: (3HGdEVGaI Edi GdGNJjGQ GdLjO ddeQNUjf(B: (3hGdJj JYJHQ ef CSGSjGJ GdJYGed GdJLGQj(B: (3aGNJjGQ GdeQNU CUHM aj hbJfG GdMGVQ CekQG aj ZGjI GdSghdI(B: (3hjQLY Pdc dJYOO GdGNJQGYGJ GdJj JJTGHI aj JMbjb GdfJjLI GdUfGYjI hcKQI GdOhd GdeUOQI ddJcfhdhLjG GdMOjKI (B: (3aGdeQNU dg de jYO eLHQG Ydi GdJYGed eY eQNU dG JhLO YfOg bGHdjI MbjbjI Hfbd GdeYQaI GdafjI (B: (3abO jYeO HYV CUMGH HQGAGJ GdGNJQGY Ydi MLH GdeYGQa GdJj dgG WGHY SQj Yf GdeQNU dg hYOe fbdgG Ch JYdjegG HGdTcd GdUMjM (B: (3eeG jLYd GdCNjQ CSjkQG ddeNJQY GdeMJcQ ddJcfhdhLjG(B: (3agPG GdfhY ef GdeQNUjf dG jfbd GdJcfhdhLjG GdMbjbjI(B: (3hEfeG jMQU Ydi hVY GdbjhO hGdTQhW GdJYSajI HUhQ hCTcGd edJhjI(B: (3eeG jVQ HeUdMI GdeQNU dg(B: (3afbd GdJcfhdhLjG jecf Cf jchf HUhQI UQjMI cJQNjU HQGAGJ GdCNJQGY(B: (3Ch bO jchf HUhQI VefjI cGfJbGd GdeYQaI hGdOQGjI ef GdehXajf GdYGedjf dOi GdeQNU dfXQGFge GdYGedjf dOi GdeQNU dg (B: (3hJYJHQ GdUhQI GdCNjQI CcKQ NWhQI(B: (3aHYV ehQOj GdJcfhdhLjG jchfhG eJQOOjf aj GYWGA eYdheGJ ObjbI HTcd hGSY ddeSJhQO NhkaG ef JBcd CQHGMge GdfGJL Yf JSQH GdJcfhdhLjG Ch JbdjOgG ef bHd GdTQcGJ GdefGaSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B369-394s
Keywords: (3GdGNJQGYGJ GdeMejI bGfhfGs; (3GdJRGeGJ eGdc HQGAI GdGNJQGYs; (3Mbhb eGdc HQGAI GdGNJQGYs; (3GJaGbjI GdJQHSs; (3JShjI GdefGRYGJs; (3GdbGfhf GdJLGQj GdeUQjs; (3GdbGfhf GdJLGQj GdchjJjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs